2016
DOI: 10.1002/hbm.23120
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal brain activation and connectivity to standardized disorder‐related visual scenes in social anxiety disorder

Abstract: Our understanding of altered emotional processing in social anxiety disorder (SAD) is hampered by a heterogeneity of findings, which is probably due to the vastly different methods and materials used so far. This is why the present functional magnetic resonance imaging (fMRI) study investigated immediate disorder-related threat processing in 30 SAD patients and 30 healthy controls (HC) with a novel, standardized set of highly ecologically valid, disorder-related complex visual scenes. SAD patients rated disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 84 publications
6
32
0
Order By: Relevance
“…Heightened functional reactivity of thalamus was also reported in several studies in which subjects with gSAD performed emotionally laden visual processing tasks. [2325] In a resting-state fMRI functional connectivity analysis by Arnold Anteraper et al, [26] hyperconnectivity of thalamus was detected with the precuneus, interior temporal, and parahippocampal regions. Findings of our study expand on the literature of thalamus dysfunction in gSAD by focusing on a more specific anatomical part of thalamus, pulvinar, and applying directed (effective) connectivity method for investigating causal dynamics of involved brain regions that to the best of our knowledge has not been used to investigate thalamus or pulvinar causal network behavior in generalized social anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Heightened functional reactivity of thalamus was also reported in several studies in which subjects with gSAD performed emotionally laden visual processing tasks. [2325] In a resting-state fMRI functional connectivity analysis by Arnold Anteraper et al, [26] hyperconnectivity of thalamus was detected with the precuneus, interior temporal, and parahippocampal regions. Findings of our study expand on the literature of thalamus dysfunction in gSAD by focusing on a more specific anatomical part of thalamus, pulvinar, and applying directed (effective) connectivity method for investigating causal dynamics of involved brain regions that to the best of our knowledge has not been used to investigate thalamus or pulvinar causal network behavior in generalized social anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported aberrant functional connectivity (FC) in SAD in DMPFC. Heitmann et al (2016) identified hyperconnectivity of globus pallidus with DMPFC during presentation of disorder-related scenes. Gimenez et al (2014) also reported differences in FC between SAD and HC in regions of medial frontal cortex.…”
Section: Discussionmentioning
confidence: 94%
“…As RPEs are a likely candidate mechanism for the modulation of connection strength between regions (den Ouden et al, 2011), another aim of the present study was to assess differences in effective connectivity between SAD and HC. In an earlier study, Heitmann et al (2016) identified aberrant functional connectivity in both DMPFC and VS in SAD. Based on their findings, we used Dynamic Causal Modelling to model dependencies between the mentalizing network and the reward network.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations